'Avoiding the certainty trap': a research programme for the policy–practice interface. (December 2015) - Paschen, Jana-Axinja; Beilin, Ruth
This paper outlines the rationale for a research focus on how meaning emerges from the interfaces between research, policy, and practice. In exploring where different constructions of risk, resilience, and landscape occur in the policy and practice discourses surrounding current developments in Victorian bushfire policy, this paper goes beyond simply advocating better science–policy–practice relationships by demonstrating the challenges of operationalising adaptive governance principles. Our findings stress that change can arise from interacting discourses on the policy–practice interface. Yet, although this may be the most adaptive moment in the policy process, producing multiple insights and alternative options, it is vulnerable to institutionalised discourses that obstruct flexible practice. Complex socioecological issues such as bushfire, we argue, require more explicit engagement with the processes of practice inherent in policy formulation. The paper offers coproductive research strategies as contributing to more flexible governance arrangements to improve adaptive policy design.